Impact of lower and higher alcohols on the physicochemical properties of particulate matter from diesel engines: A review. (June 2021) - Ghadikolaei, Meisam Ahmadi; Wong, Pak Kin; Cheung, Chun Shun; Ning, Zhi; Yung, Ka-Fu; Zhao, Jing; Gali, Nirmal Kumar; Berenjestanaki, Alireza Valipour
Abstract: The literature reveals that fossil fuels will continue to be the main energy source for transportation fleets up to 2050, despite their non-renewability and the emissions of pollutants resulting from their use. Until the full adoption of non-fossil and zero-emission vehicles (e.g., electric vehicles), the application of renewable liquid fuels could be the best choice due to the latter's positive effects such as reduced consumption of fossil fuels and reduced emissions of pollutants. Alcohols, among others, have been widely tested as alternative fuels in diesel engines, however, there is no comprehensive information about their impacts on particulate matter (PM) which has a direct influence on human health, the environment, and emission catalyst's efficiency. This review comprehensively explores the impact of lower/higher alcohols, from methanol to decanol, in dual-fuel mode on the PM physicochemical properties emitted from diesel engines under different alcohol ratios and operating conditions. It is observed that alcohols change the PM physical properties by reducing primary particle size/number, radius of gyration, fractal dimension, and fringe length and increasing fringe separation distance and tortuosity compared to those of diesel PM. Regarding the chemical properties, alcohols reduce polycyclic aromatic hydrocarbons, benzo[a]pyrene equivalent, organic carbon (OC), elemental carbon (EC), ions, and soot ignition temperature and increase OC/EC ratio and soot oxidation reactivity. Thus, each 10% of alcohol, by volume, has the potential to reduce PM mass, number, and size by about 17, 20, and 10%, while lower alcohols and blended mode have more impact than higher alcohols and fumigation mode, respectively. Graphical abstract: Image 1 Highlights: Impact of alcohols on particulate matter (PM) properties from CI engines are reviewed. PM structure and chemical properties have strong effect on PM mass, number, and size. Alcohol fuels can significantly change the physicochemical properties of diesel PM. Lower alcohols have more impact than higher alcohols on PM properties. Alcohols in blended format have more impact than fumigated format on PM reduction.